International Monetary Fund Annual Report 1953. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1953)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1953. The report highlights that despite the downward trend in world trade that became evident early in 1952, the world payments position for the year as a whole showed a much better balance than in 1951. In the latter part of 1952, there was a significant recovery, and by the beginning of 1953, many countries had again achieved balance, or at least had substantially reduced their deficits.